CASE REPORT : CONTACT TRACING ASSESSMENT AND PREVENTION OF COVID-19 IN HEMODIALYSIS UNIT HOSPITAL ROEMANI MUHAMMADIYAH SEMARANG - Langgeng Perdhana (Gorontalo State University, 2021)
Hemodialysis unit is very vulnerable place to Coronavirus Disease 2019 (Covid-19) transmission in both patients and healthcare workers. If a Covid-19 confirmed is found, it is important to conduct contact tracing, test and isolate those who are in close contact to be able to control Covid-19 transmission. In addition, it is necessary to identify problems and appropriate management to prevent transmission and the emergence of subsequent Covid-19 cases. This case report aims to explain the contact tracing assesment and prevention of Covid-19 in hemodialysis units. In this case report we describe a case of a 40-years-old man with End Stage Kidney Disease (ESKD) who underwent chronic hemodialysis and was infected with Covid-19, causing transmission to dialysis staff and other patients in the hemodialysis unit. From the search found problems including lack of consistent use of Personal Protective Equipment (PPE), ineffective screening, inadequate ventilation, and lack of compliance of visitors and patients in applying universal precaution. In conclusion, Covid-19 transmission in the hemodialysis unit can be transmitted form patient to staff, form staff to other staff, from staff to patient, and from patient to other patients. To be able to break the chain of Covid-19 transmission in hemodialysis unit, various concrete efforts must be made by dialysis staff, visitors, and patients regarding behaviour changes and environmental interventions.